2020
DOI: 10.1371/journal.pone.0235909
|View full text |Cite
|
Sign up to set email alerts
|

Association between nutritional level, menstrual-related symptoms, and mental health in female medical students

Abstract: Research suggests that medical students as well as women are at greater risk of depression compared to the general population and men. This suggests that female medical students are crucial targets requiring specific monitoring for mental health disorder prevention and intervention. However, little is known regarding the risk factors for poor mental health among this population. Therefore, we investigated whether menstrual symptoms and nutritional status are associated with psychological distress in Japanese f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 43 publications
(52 reference statements)
2
15
1
Order By: Relevance
“…Of 571 respondents evaluated in this study, 163 (28.5%) reported K-6 scores of ≥5, a value indicative of psychological distress. This percentage was higher than that identified in a previous study which revealed that 15% of Japanese female medical students had experienced psychological distress under routine conditions, 10 and another study which revealed 27% of the students had experienced depression under routine conditions. 11 The average GSES score was 29.11, with an SD of 5.36 and a Cronbach’s alpha at 0.924.…”
Section: Resultscontrasting
confidence: 68%
See 1 more Smart Citation
“…Of 571 respondents evaluated in this study, 163 (28.5%) reported K-6 scores of ≥5, a value indicative of psychological distress. This percentage was higher than that identified in a previous study which revealed that 15% of Japanese female medical students had experienced psychological distress under routine conditions, 10 and another study which revealed 27% of the students had experienced depression under routine conditions. 11 The average GSES score was 29.11, with an SD of 5.36 and a Cronbach’s alpha at 0.924.…”
Section: Resultscontrasting
confidence: 68%
“… 9 A previous cross-sectional study assessed 326 Japanese female medical students in 2018 and showed 15% of them experienced psychological distress. 10 A systematic review of 195 studies from 47 countries around the world revealed a prevalence of depressive symptoms of 27.2% among medical students 11 ; this is much higher than that reported for this age cohort among those in the general population in the USA, where the 12-month prevalence of depressive episodes has been reported at 9.3% among those in a cohort of individuals aged 18–25 years old. 12 Psychological distress was identified at the early stages of medical education, 13 as students encounter both personal and societal pressure as well as competitiveness, which is typically associated with perfectionism.…”
Section: Introductionmentioning
confidence: 93%
“…In a study by Fukushima et al carried out in a group of medical students in Tokyo, where the GHQ-30 questionnaire was also used as a tool, 85% of participants obtained a result of up to 7 points, assessed as low. In our study, only 50.30% of students obtained such a result [51]. Mohebbi et al in their research, based on the GHQ-28 result, in a group of nursing students in Iran showed that 30.0% of participants did not experience any symptoms of mental disorders, which is a result similar to our study [52].…”
Section: Discussionsupporting
confidence: 89%
“…Further the combined time required to answer all questionnaires was longer than recommended [62]. We acknowledge that some evidence supports an association of menstrual phase and mental health and that the lack of these data is a limitation of this study [63][64][65]. It is also recognized that body composition data would strengthen future studies of the relationship between diet quality and mental health.…”
Section: Discussionmentioning
confidence: 89%